Honor and shame in Western history
1 online resource.
Keywords: "This book covers a wide range of topics related to honor and shame in European historical societies: history of law and literature, social- and ancient history as well as theoretical contributions on the state of research and the importance of honor and shame in traditional societies. Honor and shame in Western history brings together fourteen texts of interdisciplinary scholars from Europe and North America. It covers a wide range of topics related to honor and shame in historical societies. The contributions cover periods of Western history from Greek and Roman times to the 19th century and many of them integrate the concept of a "Deep History" of honor and shame in social interaction. The book is essential for a broad audience interested in social history and the history of emotions"--